The effect of polymorphisms in FSHR gene on late follicular phase progesterone and estradiol serum levels in predicted normoresponders. Issue 11 (7th September 2022) - Neves, A R; Vuong, N L; Blockeel, C; Garcia, S; Alviggi, C; Spits, C; Ma, P Q M; Ho, M T; Tournaye, H; Polyzos, N P
Abstract: STUDY QUESTION: Does the presence of FSHR single-nucleotide polymorphisms (SNPs) affect late follicular phase progesterone and estradiol serum levels in predicted normoresponders treated with rFSH? SUMMARY ANSWER: The presence of FSHR SNPs (rs6165, rs6166, rs1394205) had no clinically significant impact on late follicular phase serum progesterone and estradiol levels in predicted normoresponders undergoing a GnRH antagonist protocol with a fixed daily dose of 150 IU rFSH. WHAT IS KNOWN ALREADY: Previous studies have shown that late follicular phase serum progesterone and estradiol levels are significantly correlated with the magnitude of ovarian response. Several authors have proposed that individual variability in the response to ovarian stimulation (OS) could be explained by variants in FSHR . However, so far, the literature is scarce on the influence of this genetic variability on late follicular phase steroidogenic response. Our aim is to determine whether genetic variants in the FSHR gene could modulate late follicular phase serum progesterone and estradiol levels. STUDY DESIGN, SIZE, DURATION: In this multicenter multinational prospective study conducted from November 2016 to June 2019, 366 patients from Vietnam, Belgium and Spain (166 from Europe and 200 from Asia) underwent OS followed by oocyte retrieval in a GnRH antagonist protocol with a fixed daily dose of 150 IU rFSH. All patients were genotyped for 3 FSHR SNPs (rs6165, rs6166, rs1394205) and had a serum progesterone and estradiol measurement on the day of trigger. PARTICIPANTS/MATERIALS, SETTING, METHODS: Included patients were predicted normal responder women <38 years old undergoing their first or second OS cycle. The prevalence of late follicular phase progesterone elevation (PE), as well as mean serum progesterone and estradiol levels on the day of trigger were compared between the different FSHR SNPs genotypes. PE was defined as >1.50 ng/ml. MAIN RESULTS AND THE ROLE OF CHANCE: The overall prevalence of PE was 15.8% (n = 58). No significant difference was found in the prevalence of PE in Caucasian and Asian patients (17.5% versus 14.5%). Estradiol levels on the day of trigger and the number of retrieved oocytes were significantly higher in patients with PE (4779 ± 6236.2 versus 3261 ± 3974.5 pg/ml, P = 0.003, and 16.1 ± 8.02 versus 13.5 ± 6.66, P = 0.011, respectively). Genetic model analysis, adjusted for patient age, body mass index, number of retrieved oocytes and continent (Asia versus Europe), revealed a similar prevalence of PE in co-dominant, dominant and recessive models for variants FSHR rs6166, rs6165 and rs1394205. No statistically significant difference was observed in the mean late follicular phase progesterone serum levels according to the genotypes of FSHR rs6166 ( P = 0.941), rs6165 ( P = 0.637) and rs1394205 ( P = 0.114) in the bivariate analysis. Also, no difference was found in the genetic model analysis regarding mean late follicular phase progesterone levels across the different genotypes. Genetic model analysis has also revealed no statistically significant difference regarding mean estradiol levels on the day of trigger in co-dominant, dominant and recessive models for variants FSHR rs6166, rs6165 and rs1394205. Haplotype analysis revealed a statistically significant lower estradiol level on the day of trigger for rs6166/rs6165 haplotypes GA, AA and GG when compared to AG (respectively, estimated mean difference (EMD) −441.46 pg/ml (95% CI −442.47; −440.45), EMD −673.46 pg/ml (95% CI −674.26; −672.67) and EMD −582.10 pg/ml (95% CI −584.92; −579.28)). No statistically significant differences were found regarding the prevalence of PE nor late follicular phase progesterone levels according to rs6166/rs6165 haplotypes. LIMITATIONS, REASONS FOR CAUTION: Results refer to a population of predicted normal responders treated with a normal/low fixed dose of 150 IU rFSH throughout the whole OS. Consequently, caution is needed before generalizing our results to all patient categories. WIDER IMPLICATIONS OF THE FINDINGS: Based on our results, FSHR SNPs rs6165, rs6166 and rs1394205 do not have any clinically significant impact neither on late follicular phase serum progesterone nor on estradiol levels in predicted normal responders. These findings add to the controversy in the literature regarding the impact of individual genetic susceptibility in response to OS in this population. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by an unrestricted grant by Merck Sharp & Dohme (MSD, IISP56222). N.P.P. reports grants and/or personal fees from MSD, Merck Serono, Roche Diagnostics, Ferring International, Besins Healthcare, Gedeon Richter, Organon, Theramex and Institut Biochimique SA (IBSA). C.A. reports conference fees from Merck Serono, Medea and Event Planet. A.R.N., C.B., C.S., P.Q.M.M., H.T., C.B., N.L.V., M.T.H. and S.G. report no conflict of interests related to the content of this article. TRIAL REGISTRATION NUMBER: NCT03007043.